The gut microbiota correlate with the disease characteristics and immune status of patients with untreated diffuse large B-cell lymphoma - Lin, Zhouning; Mao, Dan; Jin, Changyu; Wang, Jiaping; Lai, Yanli; Zhang, Yanli; Zhou, Miao; Ge, Qunfang; Zhang, Ping; Sun, Yongcheng; Xu, Kaihong; Wang, Yi; et al. (Frontiers in Immunology, 2023)
Background: Gut microbiota characteristics in patients with diffuse large B-cell lymphoma (DLBCL) are reportedly different when compared with the healthy population and it remains unclear if the gut microbiota affects host immunity and clinical disease features. This research investigated the gut microbiota in patients with untreated DLBCL and analyzed its correlation with patient clinical characteristics, humoral, and cell immune status. Methods: Thirty-five patients with untreated DLBCL and 20 healthy controls (HCs) were recruited to this study and microbiota differences in stool samples were analyzed by 16S rDNA sequencing. Absolute ratios of immune cell subset counts in peripheral blood were detected by flow cytometry and peripheral blood cytokine levels were detected by enzyme-linked immunosorbent assay. Relationships between changes in patient microbiomes and clinical characteristics, such as clinical stage, international prognostic index (IPI) risk stratification, cell origin, organ involved and treatment responses were investigated and correlations between differential microbiota and host immune indices were analyzed. Results: The alpha-diversity index of intestinal microecology in DLBCL patients was not significantly different when compared with HCs (P>0.05), nonetheless beta-diversity was significantly decreased (P=0.001). p_Proteobacteria were dominant in DLBCL, while p_Bacteroidetes abundance was significantly decreased when compared with HCs (P<0.05). Gut microbiota characteristics were identified that were associated with clinical features, such as tumor load, risk stratification and cell origin, and correlation analyses were performed between differential flora abundance associated with these clinical features and host immune status. The p_Firmicutes was positively correlated with absolute lymphocyte values, g_Prevotella_2 and s_un_g_Prevotella_2 were negatively correlated with absolute lymphocyte values, T cell counts and CD4 cell counts, while g_Pyramidobacter, s_un_g_Pyramidobacter, and f_Peptostreptococcaceae were negatively correlated with IgA. Conclusions: Dominant gut microbiota, abundance, diversity, and structure in DLBCL were influenced by the disease, correlated with patient immune status and this suggested that the microecology-immune axis may be involved in regulating lymphoma development. In the future, it may be possible to improve immune function in patients with DLBCL by regulating the gut microbiota, improve treatment response rates and increase patient survival rates.